2021
DOI: 10.3390/brainsci11020160
|View full text |Cite
|
Sign up to set email alerts
|

Poor Corticospinal Motor Neuron Health Is Associated with Increased Symptom Severity in the Acute Phase Following Repetitive Mild TBI and Predicts Early ALS Onset in Genetically Predisposed Rodents

Abstract: Traumatic brain injury (TBI) is a well-established risk factor for several neurodegenerative disorders including Alzheimer’s disease and Parkinson’s disease, however, a link between TBI and amyotrophic lateral sclerosis (ALS) has not been clearly elucidated. Using the SOD1G93A rat model known to recapitulate the human ALS condition, we found that exposure to mild, repetitive TBI lead ALS rats to experience earlier disease onset and shortened survival relative to their sham counterparts. Importantly, increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Next, we wanted to determine how many mild injuries were necessary to cause detectable pathology similar to what is seen on neuroimaging in patients with a history of TBI where regional encephalomalacia or brain thinning can be detected [ 30 ]. Published focal injury models and mTBI models requiring preparatory surgery ranged from 2 to 10 injuries, some occurring seconds apart while others are weeks apart [ 50 53 ]. Initial experiments were performed with 4 injuries separated 14 days apart to allow for full recovery and to test for residual long lasting effects in the second week after injury.…”
Section: Discussionmentioning
confidence: 99%
“…Next, we wanted to determine how many mild injuries were necessary to cause detectable pathology similar to what is seen on neuroimaging in patients with a history of TBI where regional encephalomalacia or brain thinning can be detected [ 30 ]. Published focal injury models and mTBI models requiring preparatory surgery ranged from 2 to 10 injuries, some occurring seconds apart while others are weeks apart [ 50 53 ]. Initial experiments were performed with 4 injuries separated 14 days apart to allow for full recovery and to test for residual long lasting effects in the second week after injury.…”
Section: Discussionmentioning
confidence: 99%
“…There is conflicting evidence of whether TBI accelerates or worsens disease in the most common animal model of ALS, which overexpresses a mutant form of human SOD1 (G93A) associated with a small number of human ALS patients. One group found that a single controlled cortical impact TBI did not affect disease onset or survival [ 123 ], but that repeated mild TBI caused earlier onset of motor symptoms, chronic motor deficits, and decreased cortical thickness in mutant SOD1 rodents [ 124 , 125 ]. However, another group found that a mild stab-wound injury to the motor cortex did not affect disease onset or progression in three different genetic rodent ALS models (SOD1, TAR DNA binding protein 43 (TDP-43), and fused in sarcoma (FUS)) [ 126 ].…”
Section: Association Of Tbi With Als and Ftdmentioning
confidence: 99%
“…The evidence supporting a role for B cells in MS, PD, and AD is strong, while in other neurological diseases such as amyotrophic lateral sclerosis (ALS), it may be a contributing factor in disease progression rather than a disease initiator. ALS is a motor neuron disease with a number of known genetic risk factors including C9orf72 repeat expansion [ 114 , 115 ]. Evidence for an inflammatory involvement includes a high expression of C9orf72 in myeloid cells, including microglia, and an increase in pro-inflammatory factors found in the spinal cords of ALS models, like the mutant Superoxide dismutase 1 gene (SOD1) mice [ 116 ].…”
Section: Further Consideration and Conclusionmentioning
confidence: 99%